Prospective Comparative Analysis Study of Minimally Invasive Surgical Decompressions versus Traditional Surgical Decompression of Carpal Tunnel Syndrome - Alkhuzai, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective: Carpal tunnel syndrome (CTS) occurs when there is compression on the median nerve within the carpal tunnel in the wrist joint. It commonly affects those who make frequent, repetitive hand movements, with women being more affected than men. The present study was aimed at comparing minimally invasive and classical surgical decompression techniques for carpal tunnel syndrome. Materials and Methods: One hundred and four patients with CTS who were scheduled for carpal tunnel decompression were chosen at random. The patients were divided into two groups. Group A had standard classical long incision decompression, whereas Group B had minimally invasive decompression. The patients were evaluated with the Boston Functional Score Scale. Between the two groups, a comparison of visit reports was made at 3, 6, and 12 months after surgery. Results: There was no significant difference in patient age (Group A was 38 years old and Group B was 36 years old) and availability of bilateral CTS status (A was 34 and B was 31). The female-male ratios in groups A and B were 3.6 to 0.2 and 3.1 to 0.3, respectively, with a p-value of p<0.05 indicating significant difference. Comparing both groups, the minimally invasive decompression technique showed a high rate of functional hand grip and a low rate of complications including early wound healing, rapid resumption of palmar strength grip, and rapid return to daily activities. Conclusion: The findings indicate that patients who underwent the minimally invasive surgical decompression one-stitch technique showed significant improvement over the traditional method.